State of Bone Health, Metabolic and Immunological Abnormalities in the Pathogenesis of Osteoarthritis in Adolescence - N.S. Shevchenko (Zaslavsky O.Yu., 2013)
In order to prevent the progression of pathological changes in the joints of adolescents with osteoarthritis we studied state of bone tissue at the initial manifestations of the disease and analyzed its relationship with biochemical, immunological and genetic characteristics. Structural and functional state of bone tissue was examined using ultrasound densitometry in 51 adolescents (31 female and 20 males) aged 12-14 years (33.3 %) and 15-18 years (67.7 %) with established diagnosis of initial stage of osteoarthritis of the knee. We have studied immunological (cellular and humoral immunity, cytokine content), biochemical (glycosaminoglycans and chondroitin sulfates in blood, uronic acid in urine, hydroxyproline excretion, the activity of acidic and alkaline phosphatase, collagenase, elastase, elastase inhibitors, content of calcium, phosphorus, magnesium) and genetic (incidence of spontaneous chromosomal aberrations) parameters. There has been revealed a significant incidence of osteopenia (60.7 %), mainly of first degree, in females under the age of 14 years in the formation of osteoarthritis on the background of reactive arthritis, reducing the height of the articular cartilage and the presence of synovitis. Analysis of the correlation of Z-score with biochemical and immunological parameters, as well as with the level of chromosomal aberrations showed a significant effect of changes in various systems of homeostasis on state of bone tissue in adolescents with osteoarthritis.